Visually impaired learning design experience through in-vitro design protocol / Rusmadiah Anwar and Verly Veto Vermol - Anwar, Rusmadiah; Vermol, Verly Veto (UiTM Press, 2020)
This paper identifies a new research area of visually impaired learning form of design, where it emerged from the literature case study that the blind community commonly have not conceived to interpret design products. Moreover, it is related to the metaphoric of semantics in design language through design thinking as a product form entity translation known as formgiving. This research article folds to structure the ecological form creation in the semiotic of product’s form orders, orientated by the extrapolative morphs design thinking. Using the in-vitro design protocol strategy that mediated through objects and haptic form understanding assessment enables the researcher to explore design attributes by its ergonomic through blind user touch experience sense.